2017
DOI: 10.1080/14681811.2017.1301904
|View full text |Cite
|
Sign up to set email alerts
|

Responsibilities, tensions and ways forward: parents’ perspectives on children’s sexuality education

Abstract: Children's sexuality education continues to be plagued with tensions and controversies. In consequence, children's access to sexuality education is severely compromised, especially in terms of the time dedicated to this topic, the content addressed, how it is taught and by whom. Based on a study of 342 Australian parents of primary school aged children we explore: (i) parents' perceptions of the relevance and importance of sexuality education to their primary school aged children and the discourses that inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 32 publications
6
80
0
8
Order By: Relevance
“…Parents seem like ideal sex educators because they can offer sex education sequentially and provide time-sensitive information as they receive questions from their children [21]. In an Australian study, parents of primary school children answered that sex education was necessary when children are young because they need to know about their bodies and to develop their own sexuality [22]. In particular, girls were considered to need sex education at a young age because their bodies develop more quickly and they could soon become vulnerable to teenage pregnancy and sexual violence [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Parents seem like ideal sex educators because they can offer sex education sequentially and provide time-sensitive information as they receive questions from their children [21]. In an Australian study, parents of primary school children answered that sex education was necessary when children are young because they need to know about their bodies and to develop their own sexuality [22]. In particular, girls were considered to need sex education at a young age because their bodies develop more quickly and they could soon become vulnerable to teenage pregnancy and sexual violence [22].…”
Section: Discussionmentioning
confidence: 99%
“…This finding also aligns with a literature review in the United States, which indicated that several factors affect sexrelated communication between parents and children, including insufficient knowledge about sex, their commitment to become more responsible sex educators for their children, the misinterpretation of discussions regarding sex as permission for the children to have sex, and the perception that their children were not old enough to discuss sex [18]. In two other studies conducted in the United States and Australia, parents thought that their children were too young to discuss sex-related issues regardless of their actual age [22,23]. If children were to learn certain information about sex before reaching sexual maturity, many parents felt that early awareness might provoke risky behaviors due to the immaturity of children's physical and mental development [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This emphasis on parents and schools is consistent with international tendencies (e.g. Robinson, Smith, and Davies 2017).…”
Section: The Politics Of Dutch Sex Educationmentioning
confidence: 71%